Explaining students' learning activity: Effects of motivation, environment, and self-efficacy - Fatmawati Samudin; Saharuna; Anas Arfandi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This research investigated the influence of motivation, learning environment, and self-efficacy on students' learning activity through an explanatory research approach. The population consisted of 3,481 vocational students in Palu City, Central Sulawesi, Indonesia, from which 359 respondents were selected using the Slovin formula and a simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed through Partial Least Squares–Structural Equation Modeling with SmartPLS 3. The assessment of the measurement model confirmed adequate validity and reliability, as all constructs met the recommended thresholds for outer loading (> 0.70), composite reliability (> 0.70), and average variance extracted (> 0.50). The structural model analysis revealed that motivation exerted a positive and significant effect on learning activity (β = 0.395; t = 4.506; p < 0.001), while self-efficacy emerged as the strongest predictor (β = 0.470; t = 6.919; p < 0.001). Conversely, the learning environment did not demonstrate a significant direct effect on learning activity (β = 0.062; t = 0.696; p = 0.487). The results indicate that internal psychological factors, particularly self-efficacy and motivation, play a more substantial role than external environmental factors in shaping students' learning activity.